2016
DOI: 10.5539/ijbm.v11n9p218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capital Structure and Managerial Ownership on Profitability: Experience from Bangladesh

Abstract: This paper aims at investigating the effects of capital structure and managerial ownership on the profitability of the Bangladeshi companies based on a strongly balanced panel data of 81 manufacturing companies listed under 10 industries in Dhaka Stock Exchange for 2002-2014. The results of Panel Corrected Standard Error (PCSE) regression model suggest that capital structure variables negatively affect ROA but positively affect ROE of the firms. Furthermore, Short term debt influences profitability of the firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
7
3
1
Order By: Relevance
“…Moreover, higher managerial ownership will align the interests between managers and shareholders. While the results of this study are not in line with Hossain(2016) where the results the research are managerial ownership has a positive effect on profitability.…”
Section: The Relationship Between Managerial Ownership and Profitabilitycontrasting
confidence: 93%
“…Moreover, higher managerial ownership will align the interests between managers and shareholders. While the results of this study are not in line with Hossain(2016) where the results the research are managerial ownership has a positive effect on profitability.…”
Section: The Relationship Between Managerial Ownership and Profitabilitycontrasting
confidence: 93%
“…However, Hossain (2016) posited that firm size does not affect the firm's profitability. This finding was conflicting and confounding.…”
Section: Firm Size and Market Valuementioning
confidence: 99%
“…According to Haque (2017), only 13 listed MNCs account for 25% of market capitalization. In the studies of Hossain (2016) and Amin and Jamil (2015), it was found that the capital structure of Bangladeshi manufacturing companies is dominated by debt as debt ratios are 57% and 55% respectively. Short term debt dominated long term debt which indicates an aggressive financing strategy.…”
Section: Problem Statementmentioning
confidence: 99%
“…After analyzing the capital structure of financial institutions of Australia, Akter (2005) found that commercial banks' debt-asset and debt-equity ratios were significantly different from NBFIs. Hossain (2016) analyzed the capital structure of 81 listed manufacturing companies and related it with profitability during 2002-2014. Like the study of Amin and Jamil (2015), they also found a very high proportion of short-term debt (42.91%) and a low proportion of long term debt (12.75%) in asset financing.…”
Section: Literature Reviewmentioning
confidence: 99%